Crystal structure of an mRNA-binding fragment of Moorella thermoacetica elongation factor SelB - Selmer, M. (Oxford University Press, 2002)
SelB is an elongation factor needed for the co-translational incorporation of selenocysteine. Selenocysteine is coded by a UGA stop codon in combination with a specific downstream mRNA hairpin. In bacteria, the C-terminal part of SelB recognizes this hairpin, while the N-terminal part binds GTP and tRNA in analogy with elongation factor Tu (EF-Tu). We present the crystal structure of a C-terminal fragment of SelB (SelB-C) from Moorella thermoacetica at 2.12 Å resolution, solved by a combination of selenium and yttrium multiwavelength anomalous dispersion. This 264 amino acid fragment contains the entire C-terminal extension beginning after the EF-Tu-homologous domains. SelB-C consists of four similar winged-helix domains arranged into the shape of an L. This is the first example of winged-helix domains involved in RNA binding. The location of conserved basic amino acids, together with data from the literature, define the position of the mRNA-binding site. Steric requirements indicate that a conformational change may occur upon ribosome interaction. Struc tural observations and data in the literature suggest that this change happens upon mRNA binding.